KAJIAN KONSEP HEALING THERAPEUTIC ARCHITECTURE PADA BALAI BESAR REHABILITASI NARKOBA BNN LIDO BOGOR - Arsitama, Albitya Helmi; Paryoko, Vijar Galax Putra Jagat (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: Drug abuse has become a serious problem in Indonesia and even around the world, with the number of addicts continuing to rise. In the period 2021 to 2023, approximately 3.3 million people in Indonesia were involved in drug abuse. One of the main causes of this phenomenon is the lack of adequate drug rehabilitation facilities in Indonesia. Most rehabilitation facilities in Indonesia only offer active detoxification of the body or medical rehabilitation, often neglecting the passive healing aspects that involve the soul and psychological awareness with the building or surrounding environment as referred to in the concept of healing therapeutic architecture. Based on this background, this research aims to examine whether the BNN Lido Drug Rehabilitation Center, which acts as a standard reference for the provision of drug rehabilitation facilities in Indonesia, has applied the principles of healing therapeutic architecture. This research uses a qualitative method with descriptive analysis. Data collection is done through literature study or secondary data. The analysis was conducted using Chrysikou's healing therapeutic architecture principles approach, resulting in the BNN Lido Drug Rehabilitation Center applying the concept including care in community, design for domesticity, social valorization, and integrated with nature. However, the application of the principle of using natural materials is still lacking. Keywords: healing therapeutic architecture, rehabilitation, drug abuse, facilities, psychology. Abstrak: Penyalahgunaan narkoba telah menjadi masalah serius di Indonesia bahkan di seluruh dunia, dengan jumlah pecandu yang terus meningkat. Pada periode 2021 hingga 2023, sekitar 3,3 juta orang di Indonesia terlibat dalam penyalahgunaan narkoba. Salah satu penyebab utama fenomena ini adalah kurangnya fasilitas rehabilitasi narkoba yang memadai di Indonesia. Sebagian besar fasilitas rehabilitasi di Indonesia hanya menawarkan detoksifikasi tubuh secara aktif atau rehabilitasi medis, seringkali mengabaikan aspek penyembuhan pasif yang melibatkan jiwa dan kesadaran psikologis dengan bangunan atau lingkungan sekitar sebagaimana disebut dalam konsep healing therapeutic architecture. Berdasarkan latar belakang tersebut, penelitian ini bertujuan untuk mengkaji apakah Balai Besar Rehabilitasi Narkoba BNN Lido yang berperan sebagai acuan standar penyediaan fasilitas rehabilitasi narkoba di Indonesia telah menerapkan prinsip healing therapeutic architecture. Penelitian ini menggunakan metode kualitatif dengan analisis deskriptif. Pengumpulan data dilakukan melalui studi literatur atau data sekunder. Analisis dilakukan dengan pendekatan prinsip healing therapeutic architecture dari Chrysikou, menghasilkan bahwa Balai Besar Rehabilitasi Narkoba BNN Lido menerapkan konsep tersebut meliputi care in community, design for domesticity, social valorization, dan integrated with nature. Namun, penerapan prinsip penggunaan material alami masih sangat kurang. Kata Kunci: healing therapeutic architecture, rehabilitasi, penyalahgunaan narkoba, fasilitas, psikologis.